الحكم القضائي الصوري: دراسة مقارنة - الكعبى، هادى حسين عبد على; عظيم، كرار معد (جامعة بابل - كلية القانون, 2019)
إن المقصود بالحكم الصوري هو الحكم الذي يصدر في خصومة وهمية ولكنها في الظاهر خصومة حقيقية، القصد منها هو إضفاء الصفة الرسمية على الاتفاقيات التي يعقدها أطراف النزاع وهذا النوع من الاتفاقات لا يمنع القانون من وقوعها طالما لم تكن الغاية منها مخالفة القانون أو النظام العام، أو بنحو الأضرار أو الغش تجاه أحد الخصوم. وبالتأكيد أن لتلك الاتفاقات عدة فوائد تعمل على تحقيقها ومنها إضفاء الصفة الرسمية على بعض العقود، كعقد الصلح حيث يعمل على حسم المنازعات بإتمام التراضي بين الطرفين، أو توثيق بعض العقود التي تتم أمام المحاكم كالإقرار أمام القاضي ببيع عين معينة بموجب عقد بيع خارجي، وتوثيقه أمام القاضي بصحة توقيعه وباستلامه كامل بدل البيع، وبذلك يكون لا يمكن الطعن فيه بالتزوير مجددا. وللأحكام الصورية عدة حالات، ولكن دراستنا سوف تقتصر على حالتين فقط هي حالة حكم التصديق على الصلح وحالة حكم رسو المزاد، فبالنسبة لأحكام الصلح فقد نظمته معظم التشريعات المقارنة ووصفته بانه عقد، ولكن القضاء كان له رأيا أخر باعتبار التصديق على الصلح من قبل القاضي حكما قضائيا، ولكنه غير حائز لحجية الأمر المقضي فيه، الأمر الذي سينعكس على قابليته على الطعن بدعوى البطلان الأصلية. نعم الصلح يعمل على أنهاء النزاع وحسم الدعوى ولا يجوز عندها تجديدها أو رفع دعوى بأبطال الصلح طالما كان موافقا للقانون، ولكن متى ما أضر الغير من ذلك الصلح أو كان مبني على الغش بقصد الأضرار بالخصم الأخر، كان لهؤلاء التمسك بأبطاله من خلال رفع دعوى مبتدأه لأبطاله حتى بعد فوات ميعاد الطعن. أما بالنسبة لحكم رسو المزاد، فهو بيع يتم تحت أشراف القضاء وبقرار صادر من قاضي التنفيذ أو المنفذ العدل فمهمة القاضي هي إيقاع البيع لمن رسا عليه المزاد، فهي لا تتعدى سوى توثيق ذلك البيع مما له الأثر البالغ في منع الطعن بهذه البيوع سواء بالغبن نظرا لإجراءاته العلنية، كذلك لا يلتزم البائع فيه بضمان الاستحقاق ولا بضمان العيوب الخفية كما في البيوع العادية، كل تلك الأمور دفعتنا إلى القول بمدى إمكانية الطعن في هذه الحكم، وهل هذا جائز قانونا؟ للإجابة على ذلك أن كل قرار قضائي معرض إلى أن يتم الطعن فيه، فقد رسم المشرع العراقي طرقا للطعن بقرار حكم رسو المزاد تتمثل بالتظلم والتمييز، أما المشرع المصري فقد اكتفى بطريق الاستئناف وبحالات محددة على سبيل الحصر، أما المشرع الفرنسي فقد شرع إلى إمكانية رفع دعوى بطلان أصليه بقصد إبطاله.
The intent of the image judgment is the judgment, which is issued, in a fictitious dispute, but it is ostensibly a real one. Its purpose is to formalize the conventions signed by the parties to the conflict. This kind of conventions do not prevent them occurred as long as it wasn't intended to break the law , public order , some damage or fraud against an opponent. Surely that these conventions have several advantages working on the relations achievement like formalization of some contracts as magistrate contract which works on resolving disputes and establishing satisfaction among the parties or complete documentation of certain contracts that are hold in the courts by confronting a Judge which includes the sale of a certain sample under external contract of sale and documented it with a Judge which entails of the validity of his signature and received full sales allowance so that no appeal is possible included a fraud again. The image provisions has several cases, but the present study will be limited to only two cases, namely, the case of the judgment on the ratification of the magistrate and the case of the moorage of auction, with regard to the provisions of the magistrate was organized by most comparative legislation as a contract, but the judiciary had another opinion on the ratification of the magistrate by the judge as a judicial provision, but he is not the owner of the authority of the expired order which reflects the ability to appeal the claim of the original invalidity. Magistrate is working on ending the conflict and resolve the case and then may not renew or sue a claim of voidance as long as it was in accordance with the law, but whenever a magistrate harmed others or was built on fraud with the intent of harming the other opponent, they had to have canceling it by suing begins with the content of voidance it even after the date of appeal. As for the moorage of auction, it is a sale done under the supervision of judiciary by a decision of a judge or justice enforcer, the task of the judge is the occurrence of the sale to those who won the auction. It is not more than just documenting of the sale, which has the great effect of preventing the appeal of such sales, whether by unfairness in view of its public procedures, in addition, the seller does not comply with the entitlement guarantee nor hidden defects' guarantee as in regular sales, all these things led us to say how the possibility to appeal this verdict and whether it is legally permissible? To answer the above question, each judicial decision is exposed to be appealed, the Iraqi legislator ways to appeal the provision verdict of auction winning represented by plaint and discrimination, whereas the Egyptian legislator had merely through appeals and specific cases exclusively, the French legislator had legislated to the possibility of genuine sue which is indented cancel it.
Keywords: الاحكام القضائية -- الاحكام الصورية -- المحاكم والقضايا -- المنازعات القضائية -- المعاملات الصورية